2019
DOI: 10.1093/jpepsy/jsz047
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Boys’ Early Childhood Exposure to Family and Neighborhood Poverty and Body Mass Index in Early Adolescence

Abstract: Objective To test relations between exposure to poverty, in the forms of family income and neighborhood deprivation, during three developmental stages, and children’s body mass index (BMI) in early adolescence. Methods Data came from a longitudinal sample of racially diverse, urban, low-income boys. Interactions between family income to needs and census-derived neighborhood deprivation at three developmental stages—early chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Previous US studies have found low agreement between individual-level and neighbourhood-level income measures, but both high individual and high neighbourhood income were associated with reduced OR of child overweight when evaluated separately 10 11. However, elsewhere a significant interaction between family-level and neighbourhood-level income has suggested that children with higher early childhood family income were at low risk of obesity in low deprivation but not high deprivation neighbourhoods 15. The independent and discordant associations between family-level income and neighborhood-level income and deprivation with child obesity among young children in Canada are unknown.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous US studies have found low agreement between individual-level and neighbourhood-level income measures, but both high individual and high neighbourhood income were associated with reduced OR of child overweight when evaluated separately 10 11. However, elsewhere a significant interaction between family-level and neighbourhood-level income has suggested that children with higher early childhood family income were at low risk of obesity in low deprivation but not high deprivation neighbourhoods 15. The independent and discordant associations between family-level income and neighborhood-level income and deprivation with child obesity among young children in Canada are unknown.…”
Section: Introductionmentioning
confidence: 88%
“…10 11 However, elsewhere a significant interaction between family-level and neighbourhood-level income has suggested that children with higher early childhood family income were at low risk of obesity in low deprivation but not high deprivation neighbourhoods. 15 The independent and discordant associations between familylevel income and neighborhood-level income and copyright. The primary objective of this study was to evaluate the independent and combined associations of family-level income, neighbourhood-level income and neighbourhood deprivation, with child obesity among children ≤12 years of age recruited from primary care practices in the Greater Toronto Area, Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation